Memory and power in post-war Europe: Studies in the presence of the past - Müller, Jan-Werner (Cambridge University, 2013)
How has memory - collective and individual - influenced European politics in the aftermath of the Second World War and the Cold War? How has the past been used in domestic and foreign policy? This book is the first to examine the connection between memory and politics directly.